Application of a Homogenous Assay for the Detection of 2, 4, 6-Trinitrotoluene to Environmental Water Samples. (2005) - Goldman, Ellen R.; Egge, Adrienne L.; Medintz, Igor L.; Lassman, Michael E.; Anderson, George P.
Abstract : A homogeneous assay was used to detect 2, 4, 6-trinitrotoluene (TNT) spiked into environmental water samples. This assay is based on changes in fluorescence emission intensity when TNT competitively displaces a fluorescently labeled, TNT analog bound to an anti-TNT antibody. The effectiveness of the assay was highly dependent on the source of the sample being tested. As no correlation between pH and assay performance was observed, ionic strength was assumed to be the reason for variation in assay results. Addition of 10x phosphate-buffered saline to samples to increase their ionic strength to that of our standard laboratory buffer (about 0.17 M ) significantly improved the range over which the assay functioned in several river water samples.